The Cognitive-Behavioural Theory and Treatment of Bulimia Nervosa: An Examination of Treatment Mechanisms and Future Directions - Lampard, Amy; Sharbanee, Jason (John Wiley & Sons, 2015)
Enhanced cognitive-behavioural therapy (CBT-E) is the current treatment of choice for bulimia nervosa. While the cognitive-behavioural theoryand treatment of bulimia nervosa have made a substantial contribution to our understanding of the disorder, approximately half of patientstreated with CBT-E fail to achieve remission of binge eating and purging. There is evidence showing that mechanisms proposed by the CBT-Emodel are associated with binge eating and purging symptoms, and therefore likely important targets for treatment. To identify future directionsin improving the efficacy of this treatment, and informed by a model of the client change process, we review the evidence for the hypothesised treatment mechanisms of CBT-E. We conclude that while the proposed treatment mechanisms of CBT-E largely change over the course of treatment, there is limited evidence that the treatment manipulations of CBT-E are responsible for the specific changes in the proposed treatment mechanisms. In addition, given a lack of research in this area, we could find no evidence that changes in the additional treatment mechanisms outlined in CBT-E are associated with changes in the core symptomatology of binge eating and purging. Based on these findings, we recommend that future efforts are directed towards understanding the client change process in CBT-E and outline three clear directions for research.